1974
DOI: 10.1677/joe.0.0620277
|View full text |Cite
|
Sign up to set email alerts
|

SPLANCHNIC, UTERINE, OVARIAN AND ADRENAL UPTAKE OF PROGESTERONE AND 20α-Dihydroprogesterone IN THE PREGNANT AND NON-PREGNANT SHEEP

Abstract: SUMMARY The uptake and extraction of progesterone and 20α-dihydroprogesterone (20α-diHP) by the splanchnic region and by some extra-splanchnic organs was measured by the determination of the concentration of labelled progesterone and 20α-diHP in a carotid artery and in the portal, hepatic, uterine, ovarian and adrenal veins during continuous intravenous infusion of [3H]progesterone. The efficiency of splanchnic extraction of progesterone and 20α-diHP was 92 and 91%. The splanchnic clearance rates of progestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…This conclusion supported previous studies on hepatic blood and clearance in cows (Wieghart et al, 1986) and ram lambs (Burrin et al, 1989). However, in contrast, Bedford et al (1974) attributed only 27% of the metabolic clearance of progesterone to hepatic uptake in the sheep, and Freetly and Ferrell (1994) did not detect any relationship between splanchnic clearance of progesterone and the level of nutrition.…”
Section: Mechanism By Which Nutrition Influences Colostrum Productionsupporting
confidence: 89%
“…This conclusion supported previous studies on hepatic blood and clearance in cows (Wieghart et al, 1986) and ram lambs (Burrin et al, 1989). However, in contrast, Bedford et al (1974) attributed only 27% of the metabolic clearance of progesterone to hepatic uptake in the sheep, and Freetly and Ferrell (1994) did not detect any relationship between splanchnic clearance of progesterone and the level of nutrition.…”
Section: Mechanism By Which Nutrition Influences Colostrum Productionsupporting
confidence: 89%
“…Therefore, we believe the decreased cytochrome P450 2C and 3A activities in the sodium propionate-supplemented animals compared to the sodium acetate-supplemented animals are most likely due to the effect of elevated insulin concentrations at the time of biopsy. Bedford et al (1972 and1974) reported metabolic clearance rates (volume of blood cleared of progesterone per unit time) for progesterone to be approximately 3.5 to 4.3 l/min in sheep. Splanchnic clearance rate of progesterone could account for 30% of total progesterone metabolism, and 70% to 90% of the total clearance of progesterone in these splanchnic organs was cleared by the liver (Bedford et al, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Bedford et al (1972 and1974) reported metabolic clearance rates (volume of blood cleared of progesterone per unit time) for progesterone to be approximately 3.5 to 4.3 l/min in sheep. Splanchnic clearance rate of progesterone could account for 30% of total progesterone metabolism, and 70% to 90% of the total clearance of progesterone in these splanchnic organs was cleared by the liver (Bedford et al, 1974). In these studies, metabolic clearance rates were determined by infusing progesterone into the peripheral circulation via the jugular vein, which is different from the in vivo source of progesterone, primarily produced in the ovary or the gravid uterus both of which are part of the portal drained viscera.…”
Section: Discussionmentioning
confidence: 99%
“…In the former study this phenomenon occurred when ovariectomized ewes were given controlled daily doses of progesterone. This effect of nutrition on plasma progesterone concentrations may be due to a higher clearance rate of progesterone since blood flow to the liver of ewes increases with feeding (Bensadoun & Reid, 1962) and the liver is a major site of progesterone catabolism (Bedford et al, 1974). If compensatory changes in secretion rate from the ovary do not occur then the peripheral progesterone concentration would be altered, and some ewes, when overfed, would have peripheral progesterone concentrations below the threshhold necessary for embryo survival.…”
Section: Discussionmentioning
confidence: 99%